String instrument choice: a study on external factors - Williams, Blair A. (Kansas State University, 2012)
An aspect of instrument choice that has not been studied in such abundance as the topics of timbre and gender associations of instruments are the influences of external factors, such as ensemble director, parent and family, friends, academic diversity, travel opportunities, and medical reasons as examples; however, these factors have been briefly addressed in word alone in many of the studies completed for related examinations. This study is integral in defining how music educators can better identify supplementary factors in addition to the timbre and gender association studies that will further influence students to choose to play an instrument and more specifically a string instrument. The findings can be applied to band, choir, theater, ROTC, and any other student organization as these factors are contributions and experiences from the student’s life previous to the presentation of the new activity. The current study focuses primarily on string instrument choice as gathered from a pilot survey using a string youth symphony ensemble from the Midwest as subjects and then high school students from three different but similar districts also in the Midwest. The information provided by the students was in agreement with previously performed studies; however, it also featured truths specifically unique to the ensemble and communities in which they were gathered. The researcher will seek to answer the following research questions: 1) What are the three most influential external factors that contributed to the student’s choice to begin string instruction? 2) How are these factors related to the musical culture of the student including opportunities for participation as well as observations? 3) Are family influences stronger than teacher/friend influences? 4) How does the strength of the string community (school and community) affect the beginning string student based on student perceptions of the two communities? Using descriptive statistics, the three most influential external factors contributing to the student’s string instrument choice in the pilot study were Parents, Private lesson teacher, and Other family. The three most influential external factors for the high school students were Parents, Live performance, and Friends. The three most influential external factors for High School #1 were Parents, Live performance, and Elementary Orchestra Teacher. For High School #2, the top three were Parents, High School Orchestra Teacher, and Friends. In High School #3, Parents, Live Performance, and Private Lesson Teacher were shown to be the student’s most influential external factors. In each case, Parents were reported as the most influential external factor for string instrument choice among the populations of students surveyed. When teachers determine recruitment activities, they must recruit the parent, which begins the moment the public school teacher is hired in the orchestra teaching position. Overall, parental influences trump all other external factors in the list examined by this population, which was slightly dissimilar than the review of the literature suggested.
Keywords: String; Instrument; Choice; External; Factors; Music (0413); Music Education (0522)